Engineering effective fibrocartilage replacement technologies using nanostructure-driven replication of soft tissue biomechanics in thermoplastic elastomer hydrogels - Lewis, Jackson Tyler, author; Bailey, Travis S., advisor; Haut Donahue, Tammy L., advisor; James, Susan P., committee member; Popat, Ketul C., committee member; Li, Yan, committee member (Colorado State University. Libraries, 2018)
Synthesis of hydrogel networks capable of accurately replicating the biomechanical demands of musculoskeletal soft tissues continues to present a formidable materials science challenge. Current systems are hampered by combinations of limited moduli at biomechanically relevant strains, inefficiencies driven by undesirable hysteresis and permanent fatigue, and recovery dynamics too slow to accommodate rapid cycling prominent in most biomechanical loading profiles. This dissertation presents a new paradigm in hydrogel design based on prefabrication of an efficient nanoscale network architecture using the melt-state self-assembly of amphiphilic block copolymers. Rigorous characterization and preliminary mechanical testing reveal that swelling of these preformed networks produce hydrogels with physiologically relevant moduli and water compositions, negligible hysteresis, sub-second elastic recovery rates, and unprecedented resistance to fatigue over hundreds of thousands of compressive cycles. By relying only on simple thermoplastic processing to form these nanostructured networks, the synthetic complexities common to most solution-based hydrogel fabrication strategies are completely avoided. Described within this dissertation are a range of efforts, broadly focused on refining synthetic and post-synthetic processing techniques to improve the modulus, surface hydrophilicity, fatigue resistance and cytocompatibility of these thermoplastic elastomer hydrogels, with the ultimate goal of producing a material viable as a meniscal replacement.
Keywords: fatigue-resistant; soft tissue mimic; block copolymer; thermoplastic; hydrogel